Openness in creating a development path of a tourism-focused city - Rynio, Dorota (Otwartość w kreowaniu ścieżki rozwoju miasta ukierunkowanego na turystykę, 2019)
The wealth of societies, a well-developed infrastructure of domestic tourism and global accessibility, surplus of free time determine the increased flow of tourists in the world economy. Attractive locations are not prepared to accommodate such a large number of people. Hence, the continued application of the existing strategies in these places is becoming a problem. The need arises to change the strategy from a quantitative to a qualitative one based on customer segmentation. At the moment, the most popular tourist destinations must use a system of tools limiting access to the settlement unit in order to implement the idea of sustainable tourism. The aim of the paper is to indicate the multifaceted consequences of opening up the city in conditions of the changing economy. The following research methods were used: studies of domestic and foreign literature, benchmarking and simple statistical methods. The analysis concerns the contemporary conditions, in which cities strive to implement the idea of sustainable tourism
Biblioteka Regionalisty, 2019, Nr 19, s. 198-208
Keywords: Dolny Śląsk